Liquid crystal-polymer composites switchable windows for radiant energy flow and privacy control - Halder, Suman; Shin, Yunho; Zhou, Ziyuan; Zhang, Xinfang; Hu, Lang; Yang, Deng-Ke (Frontiers in Soft Matter, 2022)
Global warming is becoming a more and more severe crisis for humans. One way to resolve the concern is to reduce energy consumption. Smart switchable windows for office and residential buildings and vehicles can help reduce energy consumption. An ideal smart window should be able to control radiant energy flow and privacy. We investigated the capability of switchable windows based on liquid crystal/polymer composites, such as polymer dispersed liquid crystal (PDLC), polymer stabilized liquid crystal (PSLC), and polymer stabilized cholesteric texture (PSCT), to control the privacy and radiant energy flow. Through a systematic study, we identified methods to improve their capabilities. We demonstrated that PDLC and PSCT windows of sufficient thick film thickness can control both privacy and energy flow.